Effects of reducing the number of candidate tasks in voluntary task switching - Kleinsorge, Thomas; Scheil, Juliane (Frontiers in Psychology, 2015)
Recently, Demanet and Liefooghe (2014, Experiment 3) reported an experiment on voluntary task switching in which the number of candidate tasks to choose from was reduced from four to two before participants indicated their task choice. This procedure was intended to prevent participants from choosing a task in advance of the presentation of a prompt to do so. This procedure is highly similar to a procedure recently employed by Kleinsorge and Scheil (in press) in a study of cued task switching which yielded evidence for a selective facilitation of task switches by a reduction of the number of tasks to two. In order to examine whether a similar effect would also be observed with voluntary task switching, we conceptually replicated the experiment of Demanet and Liefooghe with an additional control condition in which the number of tasks was not reduced. In this experiment, no evidence for a facilitation of task switching could be observed, pointing to a functional divergence between explicit task cues and the internally generated cues involved in voluntary task switching. In addition, we observed evidence for a selective advantage of forced switch trials over repetition-possible trials that was largely independent of the duration of the preparation interval. This effect was accompanied by a massive increase of task indication times in conditions with a reduced number of tasks, suggesting that this manipulation resulted in a pronounced change in the way participants performed voluntary task switches.